2016
DOI: 10.3389/fpsyg.2016.01105
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Meta-Emotional Problem Decreases Physiological Fear Response during Exposure in Phobics

Abstract: Anxiety disorders may not only be characterized by specific symptomatology (e.g., tachycardia) in response to the fearful stimulus (primary problem or first-level emotion) but also by the tendency to negatively evaluate oneself for having those symptoms (secondary problem or negative meta-emotion). An exploratory study was conducted driven by the hypothesis that reducing the secondary or meta-emotional problem would also diminish the fear response to the phobic stimulus. Thirty-three phobic participants were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 45 publications
2
13
0
1
Order By: Relevance
“…There is evidence that trait self-criticism is a trans -diagnostic phenomenon implicated in the development and maintenance of a range of psychopathologies ( Schanche, 2013 ) as it triggers, perpetuates, and intensifies emotional reactivity ( Shahar, 2013 ). However, the key difference between self-criticism and the meta-emotional problem is that in the latter patients only criticize themselves for having a specific emotion, whereas self-criticism refers to all aspects of a patient’s life ( Couyoumdjian et al, 2016 ). A more direct relation between the meta-emotional problem and anxiety symptomatology has been empirically tested by ( Wells, 2000 ) who applied his Metacognitive Therapy in the context of both generalized and social anxiety.…”
Section: Authors’ Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence that trait self-criticism is a trans -diagnostic phenomenon implicated in the development and maintenance of a range of psychopathologies ( Schanche, 2013 ) as it triggers, perpetuates, and intensifies emotional reactivity ( Shahar, 2013 ). However, the key difference between self-criticism and the meta-emotional problem is that in the latter patients only criticize themselves for having a specific emotion, whereas self-criticism refers to all aspects of a patient’s life ( Couyoumdjian et al, 2016 ). A more direct relation between the meta-emotional problem and anxiety symptomatology has been empirically tested by ( Wells, 2000 ) who applied his Metacognitive Therapy in the context of both generalized and social anxiety.…”
Section: Authors’ Hypothesismentioning
confidence: 99%
“…Moreover, a recent study directly tested whether reducing the negative assessment of specific negative emotions related to phobic stimuli (i.e., secondary problem) also reduced the experience of the aversive emotion itself (i.e., primary problem). Results revealed that participants whose meta-emotional problem was addressed during therapy also presented a decrease in autonomic arousal (as observed by decreased heart rate and increased heart rate variability) during a second exposure to phobic stimuli ( Couyoumdjian et al, 2016 ). Furthermore, the meta-emotional problem is considered to play a role in affective disorders.…”
Section: Authors’ Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the studies outlined above have indicated that autonomic flexibility (i.e., reactivity) depends on the baseline level of RSA (Friedman and Thayer 1998;Beauchaine 2001;Rottenberg et al 2007;Couyoumdjian et al 2016). High baseline RSA was associated with a decline in RSA and subjects with low baseline RSA had the opposite reaction to stress.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a higher level of autonomic flexibility was typical for anxious boys. Moreover, there are a growing number of observations that do not fit the theories of Thayer and Porges (Kossowsky et al 2012;Gorka et al 2013;Fortunato et al 2013;Wang et al 2013;Kristensen et al 2014;Spangler et al 2015;Couyoumdjian et al 2016;Fung et al 2017). One possible explanation for this disagreement could be the influence of individual differences in autonomic control and autonomic flexibility on RSA reactivity (Berntson and Cacioppo 2004).…”
Section: Introductionmentioning
confidence: 99%